EXPERIMENTAL INVESTIGATION OF THE INDUSTRIAL CHILLS HEATING PROCESSES AND THE WAYS OF APPRAISAL O F THEIR FASTNESS - A. N. Chichko; T. V. Matjushinets; L. V. Markov; V. F. Sobolev (Литьë и металлургия)
The dynamics of the temperature changing in allocated points of industrial chill molds is experimentally investigated. It is shown that one of the reasons of the chill mold fastness decrease may be prolonged being in nonstationary regime of “working”, what is connected with its three-dimensional configuration and different-walled.